Between Two Worlds. German Travellers in Spain and Morocco in the 19th Century - Raposo, Berta (Revista de Filología Alemana, 2014)
Travel literature, as an optimal vehicle for the documentation of intercultural relationships, gives us many examples of analogical, antithetic and reciprocal typology. In the case of German travellers whose destination was originally Spain, but who also visited Morocco for several reasons, the perception of those differences uses to be twofold, as we will try to show in the following paper. In most of the cases of the typology shown in these stories about travelling, Spain turns out to be the point of departure more than Germany. The analogical and reciprocal typologies are barely present since Germany (the land of origin) is too far away for the travellers.